Оптимизация структуры потребления первичных энергоресурсов - Половян, А.В. (Економіка промисловості, 2015)
Предложен методический подход, который позволяет при заданной технологии производства определить оптимальные значения потребления первичныхэнергоресурсов. В основу данного подхода положена трансцендентно-логарифмическая функция. Полученную систему уравнений предложено решать с помощью метода множителей Лагранжа. Проведено сценарное моделирование для металлургического комплекса Украины. Запропоновано методичний підхід, який дозволяє при заданій технології виробництва визначити оптимальні значення споживання первинних енергоресурсів. В основу даного підходу покладено трансцендентно-логарифмічну функцію. Отриману систему рівнянь запропоновано вирішувати за допомогою методу множників Лагранжа. Проведено сценарне моделювання для металургійного комплексу України. The consumption of different types of energy is the basis for a modern economy. Energy is one of the basic sectors of the economy. It ensures the smooth functioning of economic development. Questions to optimize the structure of energy consumption, which can reduce energy costs with existing technology, are poorly understood, despite the significant research results in the formation of an effective energy policy. Methodical approach suggested in the paper that allows a given production technology to determine the values of primary energy consumption, which optimize energy costs. Translog function is the basis of this approach. It allows determining the elasticity‟s between the main factors that influence energy consumption taking into account existing technology. The function cost energy costs determined on the basis of the duality theorem. The resulting system of equations allows finding the value of individual consumption of primary energy and the minimum of the total costs in terms of value for a given technology. The solution to this problem is to coordinate the point of tangency constraints and the objective function. The resulting system of equations is proposed to be solved by the method of Lagrange multipliers, which allows determining the optimal values of the individual energy consumption. The metallurgical complex of Ukraine is considered as an example of the practical application of the proposed approach. Parameter estimation equations of the relationship of total consumption by the official and shadow volumes of sales to the metallurgical enterprises of Ukraine, as well as the energy consumption of individual are given. The equation of energy consumption in value depending on the price of individual energy is rated. These equations allow reflecting the current level of technology and replacement and can be used to find the values of natural gas and coal, which optimize the cost of their purchase. Scenario simulations conducted, which is associated with changes in the prices for natural gas and coal in Ukraine. Optimal direction of the change in the structure of primary energy consumption is revealed. Main advantages and disadvantages of this approach are analyzed.